Sobrevivência e desenvolvimento de espécies de Spodoptera (Lepidoptera: noctuidae) em soja expressando Cry1Ac e Cry1F e implicações no manejo da resistência - Machado, Eduardo Perkovski (2020)
Species of the genus Spodoptera have caused significant damage to soybean, Glycine max (L.) Merril in Brazil. Among these species, stand out Spodoptera frugiperda (Smith, 1797), Spodoptera eridania (Stoll, 1782), Spodoptera cosmioides (Walker, 1858) and Spodoptera albula (Walker, 1857). Recently, a new genetically-modified soybean technology that expresses Cry1Ac and Cry1F (event DAS-81419-2) proteins has been released for commercial use in Brazil, which may be an option for the management of these species. Here, were conducted studies to evaluate the survival and development of resistant S. frugiperda strains selected on Bt-maize single (Cry1F) and pyramided (Cry1F/Cry1A.105/Cry2Ab2) events and F1 hybrids (heterozygotes) of the selected and susceptible strains on genetically-modified soybeans (event DAS-81419-2) expressing Cry1Ac and Cry1F. Were also evaluate the survival, development and population growth of S. eridania, S. cosmioides and S. albula on Cry1Ac/Cry1F-soybean. In the first study, susceptible insects of S. frugiperda did not survive on Cry1Ac/Cry1F-soybean. However, homozygous-resistant and heterozygous insects were able to survive and emerge as fertile adults when fed on Cry1Ac/Cry1F-soybean. Life history studies revealed that homozygous-resistant insects had similar development, reproductive performance and population increases on Cry1Ac/Cry1F-soybean and non-Bt soybean. In contrast, heterozygotes had their fertility life table parameters significantly reduced on Cry1Ac/Cry1F-soybean. In the second study, Spodoptera eridania and S. cosmioides showed long development time and low larval and egg-to-adult survival when developed on Cry1Ac/Cry1F-soybean. This negatively affected the population growth of these species. S. albula also had low larval survival and number of insects that reached adulthood on Cry1Ac/Cry1F-soybean. However, no significant effects of Cry1Ac/Cry1F-soybean on population growth parameters of this species were detected. In summary, S. frugiperda resistance to Cry1F (single) and Cry1F/Cry1A.105/Cry2Ab2 (pyramided) maize negatively affects the efficacy of Cry1Ac/Cry1F-soybean. Therefore, the selection of S. frugiperda for resistance to single and pyramided Bt maize can result in cross-crop resistance to Cry1Ac/Cry1F-soybean. The Cry1Ac/Cry1F-soybean also reduces the survivorship and population growth of S. eridania and S. cosmioides causing population suppression of these species. However, this Bt soybean has no relevant effect on the survival and population growth of S. albula.